2023
DOI: 10.1002/advs.202301919
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Propelled Enzymatic Nanomotors from Prodrug‐Skeletal Zeolitic Imidazolate Frameworks for Boosting Multimodel Cancer Therapy Efficiency

Abstract: Self-propelled nanomotors, which can autonomous propelled by harnessing others type of energy, have shown tremendous potential as drug delivery systems for cancer therapy. However, it remains challenging for nanomotors in tumor theranostics because of their structural complexity and deficient therapeutic model. Herein, glucose-fueled enzymatic nanomotors (GC6@cPt ZIFs) are developed through encapsulation of glucose oxidase (GOx), catalase (CAT), and chlorin e6 (Ce6) using cisplatin-skeletal zeolitic imidazolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…29 In some enzyme-driven MNMs, magnetic materials will also be added to control their movement direction to achieve targeted drug delivery as well as to enhance photodynamic therapy. 30,31 Enzyme-driven MNMs can also be used to detect DNA. 32 It is also feasible to apply the activity of double enzyme to MNMs.…”
Section: Chemical Reactions Propel Mnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In some enzyme-driven MNMs, magnetic materials will also be added to control their movement direction to achieve targeted drug delivery as well as to enhance photodynamic therapy. 30,31 Enzyme-driven MNMs can also be used to detect DNA. 32 It is also feasible to apply the activity of double enzyme to MNMs.…”
Section: Chemical Reactions Propel Mnmsmentioning
confidence: 99%
“…Enzyme-driven MNMs have become promising devices in biomedicine due to their good biocompatibility and versatility as well as the high bioavailability of fuels . In some enzyme-driven MNMs, magnetic materials will also be added to control their movement direction to achieve targeted drug delivery as well as to enhance photodynamic therapy. , Enzyme-driven MNMs can also be used to detect DNA . It is also feasible to apply the activity of double enzyme to MNMs .…”
Section: Micro/nanomotors Are Propelled By Different Energiesmentioning
confidence: 99%
“…The Pearson's correlation coefficient for HTiPC nanomotor was ∼0.32, lower than that of HTiP (∼0. 46).…”
Section: Synthesis and Characterization Of The Janus Htipcmentioning
confidence: 99%
“…For example, incorporation of oxygen carrier for targeted delivery, in situ decomposition of H 2 O 2 using enzyme and catalyst, biomimetic photosynthesis of oxygen, inhibition of cell respiration, and surface modification with an active targeting ability. [55,128] The therapeutic efficiency of PDT is inhibited by the hypoxia microenvironment of tumor tissues. To reverse this issue, Xiao et al reported a novel oxygen evolving MOF complex through coating with a thin MnO 2 layer and cancer cell membrane for hypoxia reversion and active target (Figure 11A).…”
Section: Cancer Therapymentioning
confidence: 99%